Fabrication of Pickering emulsions stabilized by citrus pectin modified with β-cyclodextrin and its application in 3D printing. (15th July 2023) - Cen, Shaoyi; Li, Zhihua; Guo, Ziang; Shi, Jiyong; Huang, Xiaowei; Zou, Xiaobo; Holmes, Melvin
Abstract: Pickering emulsions stabilized by polysaccharide particles have received increasing attention because of their potential applications in three-dimensional (3D) printing. In this study, the citrus pectins ( citrus tachibana, shaddock, lemon, orange) modified with β-cyclodextrin (β-CD) were used to stabilize Pickering emulsions reaching the requirements of 3D printing. In terms of pectin chemical structure, the steric hindrance provided by the RG I regions was more conducive to the stability of the complex particles. The modification of pectin by β-CD provided the complexes a better double wettability (91.14 ± 0.14°-109.43 ± 0.22°) and a more negative ζ-potential, which was more beneficial for complexes to anchor at oil-water interface. In addition, the rheological properties, texture properties and stability of the emulsions were more responsive to the ratios of pectin/β-CD (Rβ/C ). The results showed that the emulsions stabilized at a φ = 65 % and a Rβ/C  = 2:2 achieved the requirements (shear thinning behavior, self-supporting ability, and stability) of 3D printing. Furthermore, the application in 3D printing demonstrated that the emulsions under the optimal condition (φ = 65 % and Rβ/C  = 2:2) displayed excellent printing appearance, especially for the emulsions stabilized by β-CD/LP particles. This study provides a basis for the selection of polysaccharide-based particles to prepare 3D printing inks which may be utilized in food manufacturing. Graphical abstract: Unlabelled Image